Analisis Selisih Biaya Produksi Sebagai Alat Pengendalian Manajemen dalam Meningkatkan Efisiensi Biaya Produksi - Iriyadi, Iriyadi (Jurnal Ilmiah Ranggagading (JIR), 2005)
Differential analysis holds a very important role in controlling the production cost of a company. It can, among other things, measure cost efficiency by implementing comparison between standard cost and actual cost. With the analysis we can identify the cause of standard cost and actual cost deviation. Then the management of the company can take recovery action as well as control the cost deviation. Key words : Production Cost Analysis; Management Control; Production Cost.